Language and World. Part Two. Signs, Minds and Actions - Puhl, Klaus (Publications of the Austrian Ludwig Wittgenstein Society - New Series (N.S.), 2010)
This second of two volumes brings together invited papers of the 32nd International Wittgenstein Symposium (Kirchberg/W. (Austria), 2009). The collection not only contains articles related to some of Wittgenstein's central arguments but also holds contributions that deal with the role and function of signs, as well as with the relations between language and action, consciousness and metaphysics. An interdisciplinary workshop was dedicated to "Wittgenstein and Literature", an area of study which has been prominent in the philosophical discourse of the last decade. Contributors to this volume are Anat Biletzki, Michael Dummett, Laurence Goldstein, Peter Janich, Brian McGuinness, Marjorie Perloff, David Schalkwyk, Joachim Schulte, Pirmin Stekeler-Weithofer, David Stern, Eike von Savigny among others.